Subacute toxicity of isoliquiritigenin-zein phosphatidylcholine nanoparticles on biochemical, hematological, and histopathological parameters in Sprague-Dawley rats - Ke Yang; Kumar Ganesan; Fei Gao; Chunguang Xie; Jianping Chen (Exploration of Drug Science)
Aim: Isoliquiritigenin (ISL) is a natural flavonoid found in many natural plants, which exhibits numerous pharmacological properties including anti-inflammatory, antioxidant, antitumor, and antiviral activities. However, the low bioavailability and stability of ISL limit its application in clinical practice. To overcome these limitations, ISL-zein phosphatidylcholine hybrid nanoparticles (ISL@ZLH NPs) have been developed to improve the bioavailability and stability of ISL. The present study aimed to evaluate the acute and subacute toxicity of ISL@ZLH NPs in Sprague-Dawley (SD) rats. Methods: The ISL@ZLH NPs were prepared by the solvent evaporation method. The acute toxicity was evaluated by administering a single dose of 110 mg/kg and 160 mg/kg of ISL@ZLH NPs extracted in distilled water via oral gavage in rats and mice, respectively. The subacute toxicity was evaluated by administering doses of 27.5 mg/(kg∙day), 55 mg/(kg∙day), and 110 mg/(kg∙day) of ISL@ZLH NPs for 30 days and 90 days. The biochemical, hematological, and histopathological parameters were analyzed in both studies. Results: In the acute toxicity study, no mortality or significant changes in the biochemical and hematological parameters were observed in both Kunming (KM) mice and SD rats. In the subacute toxicity study, no toxic reactions were observed in both species at all doses tested. Moreover, no significant changes in the biochemical, hematological and histopathological parameters were observed in both species. Conclusions: The results of this study suggest that ISL@ZLH NPs are safe and non-toxic in both KM mice and SD rats. The nanoparticles (NPs) did not induce any adverse effects on the biochemical, hematological, and histopathological parameters in both acute and subacute toxicity studies. These results indicate that ISL@ZLH NPs are safe for prolonged consumption. Further studies are needed to evaluate the long-term toxicity and efficacy of these NPs in vivo.